2002
DOI: 10.1128/jb.184.4.904-912.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Cell Division Protein FtsW Is Required To Recruit Its Cognate Transpeptidase, FtsI (PBP3), to the Division Site

Abstract: The bacterial cell division protein FtsW has been suggested to perform two functions: stabilize the FtsZ cytokinetic ring, and facilitate septal peptidoglycan synthesis by the transpeptidase FtsI (penicillin-binding protein 3). We show here that depleting Escherichia coli cells of FtsW had little effect on the abundance of FtsZ rings but abrogated recruitment of FtsI to potential division sites. Analysis of FtsW localization confirmed and extended these results; septal localization of FtsW required FtsZ, FtsA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 46 publications
5
163
0
Order By: Relevance
“…Interestingly, FtsW and FtsN also interacted strongly with each other, as reported recently in E. coli (Alexeeva et al 2010). Although SidA did not interact with full-length FtsI, neither did FtsW (data not shown), as expected based on studies in E. coli (Mercer and Weiss 2002). We therefore tested a truncated version of FtsI (FtsIDC) lacking its periplasmic catalytic domain.…”
Section: Sida Resides In the Inner Membrane And Interacts Directly Wimentioning
confidence: 93%
“…Interestingly, FtsW and FtsN also interacted strongly with each other, as reported recently in E. coli (Alexeeva et al 2010). Although SidA did not interact with full-length FtsI, neither did FtsW (data not shown), as expected based on studies in E. coli (Mercer and Weiss 2002). We therefore tested a truncated version of FtsI (FtsIDC) lacking its periplasmic catalytic domain.…”
Section: Sida Resides In the Inner Membrane And Interacts Directly Wimentioning
confidence: 93%
“…Prior to its assembly at midcell, C. crescentus FtsZ has been shown to localize at the stalk pole (38). This event makes FtsZ an intriguing candidate as a recruiter of DivJ based on the observation in E. coli that FtsZ is required for the recruitment of FtsA, which in turn is needed to recruit additional division proteins such as FtsN and FtsW (1,24,26,47). Similarly, in B. subtilis, FtsZ is required to recruit the DivIB and DivIC proteins to the division septum (22).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence microscopy has shown that in E. coli during the later stages of cell growth FtsI localizes to the division site at the septum. The septal localization of FtsI, however, depends upon prior localization of the other cell division proteins, such as FtsZ, FtsA, FtsK, FtsQ, FtsL and FtsW (Mercer & Weiss, 2002;Weiss et al, 1999), and therefore, it appears that FtsI is a late recruit to the division site. In B. subtilis, the septal localization of PBP3/FtsI is also delayed, but is needed for the localization of the division inhibitor MinC (Marston & Errington, 1999).…”
Section: Introductionmentioning
confidence: 99%